Implementation Of Murabahah Contracts and Sharia Compliance in Islamic Financial Institutions - Alhadiansyah, Alhadiansyah; Marnita; Fitria, Laili (ASAS, 2025)
This study examines legal issues concerning the implementation of murabahah contracts in Islamic financial institutions in Indonesia from the perspective of Islamic contract law. Murabahah is the most dominant financing instrument in Islamic banking, accounting for more than half of total financing portfolios. However, its operational practices often diverge from the normative requirements established by Islamic law, the fatwas of the National Sharia Council (DSN–MUI), and statutory regulations. Employing a normative legal research method with statutory, conceptual, and Islamic jurisprudential approaches, this study identifies several recurring legal problems, including the use of conventional interest benchmarks in margin determination, improper application of murabahah bil wakalah, and the rescheduling of payment obligations with additional margins. These practices potentially introduce elements of riba, gharar, and unjust enrichment, thereby undermining the validity of the contract under Islamic law. The study argues that non-compliance with sharia principles renders murabahah contracts legally defective and contradicts the objectives of Islamic law (maqāṣid al-sharī‘ah). This research contributes by offering a systematic legal analysis of sharia compliance gaps in murabahah practices and proposing normative recommendations for operational standardization and strengthened sharia supervision.